Country-Specific Modeling of Methane Production and Emission Reduction Utilizing Pig Manure - Ilho Bae; Seokbo Park; Juhee Shin; Jin Mi Triolo; Seung Gu Shin (Energies)
The purpose of this study is to effectively support the operation of biogas plants that utilize anaerobic digestion of pig manure. An analysis was conducted on the characteristics of manure collected from 17 pig farms. Following this, the methane potential of the manure was evaluated, and a comparison of microbial communities was made at the end of the biochemical methane potential test. Based on these analyses, methane production during anaerobic digestion was modeled under various scenarios, allowing for the calculation of expected electricity generation and carbon dioxide reduction. The experimental results were categorized according to manure management type and the types of pigs raised. In this study, at a temperature of 37 °C and a hydraulic retention time of 30 days, the scraper method demonstrated the highest methane production rates, achieving 0.85 and 1.03 m3/m3/day for both mono-anaerobic digestion of manure and co-digestion with food wastewater. However, establishing definitive characteristics of manure management types requires the collection of more comprehensive data from a broader range of farms, which will be critical for conducting further in-depth research.